Quaternary caldera-forming eruptions at the Sanzugawa caldera, NE Japan, revealed by zircon U-Pb geochronology - Ito, Hisatoshi (Frontiers in Earth Science, 2023)
Recent application of zircon U-Pb geochronology has contributed to deciphering the evolution of caldera systems worldwide. However, in the Tohoku region, NE Japan, this is not the case, although it is well studied as a typical island arc subduction system. Here, U-Pb dating of zircon suggests that the Sanzugawa caldera, the largest caldera in Tohoku since late Miocene, initiated its caldera-forming volcanic activity at ~7 Ma and confirms the activity culminated in late Pliocene to Quaternary (3.0−1.5 Ma). This is contrary to a previous notion that the caldera developed in late Miocene to Pliocene (6−3 Ma) based on mainly whole-rock K-Ar dating results. This finding may also contradict a current hypothesis of relatively subdued volcanism at 3.5−1.5 Ma in NE Japan and thus shows the need to date other calderas in the Tohoku region with zircon U-Pb and/or Ar-Ar methods to better understand the magmatic history of this region.